1991
DOI: 10.1302/0301-620x.73b6.1955442
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease and silent avascular necrosis of the hip

Abstract: We reviewed the prevalence of avascular necrosis (AVN) in a series of patients with sickle cell disease, using radiography and magnetic resonance imaging. We found AVN of at least one hip in 11 of 27 patients (41%). This is a significantly greater prevalence than reported. MRI was not as helpful in patients with sickle cell disease as it is in patients with AVN from other causes; it detected no more cases than radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Despite these limitations, the literature suggests that, in general, the various techniques are comparable. [5,7,8,9] The outcomes of patients treated at our institution as well as other reported outcomes in the literature suggest that core decompression and non-vascularized bonegrafting techniques are viable options to avert the need for additional surgery in patients with early stage osteonecrosis of the hip. Hence, the present study was conducted to compare functional outcome of percutaneous decoring and grafting versus decoring and fibular graft insertion in patients of avascular necrosis of head of femur.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Despite these limitations, the literature suggests that, in general, the various techniques are comparable. [5,7,8,9] The outcomes of patients treated at our institution as well as other reported outcomes in the literature suggest that core decompression and non-vascularized bonegrafting techniques are viable options to avert the need for additional surgery in patients with early stage osteonecrosis of the hip. Hence, the present study was conducted to compare functional outcome of percutaneous decoring and grafting versus decoring and fibular graft insertion in patients of avascular necrosis of head of femur.…”
Section: Introductionmentioning
confidence: 87%
“…It is essential that AVN of the femoral head is diagnosed early because delaying this disease by joint preserving measures have a much better prognosis and because the results of joint replacement are poorer in young individuals. [2,3,4,5,6,7] AVN can be managed using operative and nonoperative techniques. The non-operative treatments reported in the literature include pharmacological therapy, extracorporeal shockwave therapy, and electromagnetic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding is not in agreement with the recent studies on SCD that have suggested a lower prevalence (26%) of AVN among children with Hb SS (mean age, 9.8 years) compared to adults (48.6%) with a mean age of 26.7 years. In a study by Ware et al 41% of adults with Hb SS over the age of 15 years had bone AVN [17]. However, Koduri et al reported that silent AVN occurred in 41% children aged 4-28 years with the spine and shoulder being involved in 27% and 28% cases, respectively [18].…”
Section: Effectmentioning
confidence: 98%
“…Epiphyseal infarction has a predilection for the head of the femur (avascular necrosis), followed by the humorous, knee, and the small joints of the hands and feet (Jean-Baptiste and De Ceulaer, 2000;Lonergan et al, 2001). A significant number of HbSS patient develop epiphyseal osteonecrosis (Styles and Vichinsky, 1996;Ware et al, 1991), bone infection (Almeida and Roberts, 2005;Neonato et al, 2000), and transient red cell aplasia (abnormal decrease of reticulocytes) (Goldstein et al, 1987;Serjeant et al, 2001). …”
Section: Bone and Joint Complicationsmentioning
confidence: 99%